Internal Capital Markets in Business Groups and the Propagation of Credit Supply Shocks - Shi, Yu (IMF Working Papers; Working Paper ;, 2019)
Using business registry data from China, we show that internal capital markets in business groups can propagate corporate shareholders' credit supply shocks to their subsidiaries. An average of 16.7% local bank credit growth where corporate shareholders are located would increase subsidiaries investment by 1% of their tangible fixed asset value, which accounts for 71% (7%) of the median (average) investment rate among these firms. We argue that equity exchanges is one channel through which corporate shareholders transmit bank credit supply shocks to the subsidiaries and provide empirical evidence to support the channel.